Control synthesis of low aspect ratio Zn1-xAgxO nanorods using low temperature solution route: Evidence of Ag concentration dependent shape transition. (April 2022) - Mukherjee, Sumit; Pramanik, Subhamay; Das, Sandip; Bhattacharjee, Gaurab; Mondal, Shyamal; Ghosh, Tatan; Chattopadhyay, Amarnath; Sao, Dilip; Nath, Rajib; Kuiri, Probodh K.
Highlights: Control synthesis of low aspect ratio of Zn1-x Agx O nanorods at low temperature is achieved. A shape transition from sphere to rod takes place in Zn1-x Agx O nanoparticles for Ag concentration of 2 mol%. Length of Zn1-x Agx O nanorods increases with increase in Ag concentration. Anomalous behavior of structural, optical, and antimicrobial properties are observed near the shape transition point. A decrease in band gap of Zn1-x Agx O nanoparticles is seen with increase in Ag concentration. Abstract: Understanding the effect of doping concentration on the various properties of metal-doped ZnO nanoparticles (NPs) near the shape transition point (sphere to the rod) is essentially required for their possible applications. Given these, we have successfully synthesized spherical to rod-shaped Zn1-x Agx O employing a simple chemical route considering Ag doping with concentrations of 1, 2, and 3 mol percentage (%). Although, the shape transition from spherical to rod has been triggered at doping concentration of 2 mol%, the shape transition has been found to be completed for 3 mol% generating nanorods with an aspect ratio of ∼1.33. Structural, optical, and antimicrobial properties of Zn1-x Agx O NPs show significant changes at the transition concentration of Ag. The shape transition occurs mainly due to the process of synthesis and change in the surface states of the NPs in presence of excess Ag + ions in the local environment of the nucleation sites of ZnO. Graphical abstract: Image, graphical abstract